Caracterização nutricional e investigação microbiológica da Bottarga produzida pela comunidade pesqueira da Enseada da Baleia – Cananéia, SP - Mota, Raphaella Revolti (Universidade Estadual Paulista (Unesp), 2024)
Os produtos produzidos de maneira conhecida como eco-friendly e que estão alinhados com ao menos um dos Objetivos de Desenvolvimento Sustentável da Organização das Nações Unidas captam imediatamente a atenção de um número crescente de consumidores. É nesse contexto que se encontra a bottarga de tainha, produzida artesanalmente pela comunidade pesqueira da Enseada da Baleia, Cananéia – SP. O objetivo deste trabalho foi caracterizar a composição química e realizar investigação microbiológica da bottarga produzida pela comunidade da Enseada da Baleia. O estudo apresentou os resultados de umidade (8,82%); cinzas (7,92%); proteína bruta (43,56%); lipídios (19,59%); sólidos totais (91,18%); pH (5,7); bases nitrogenadas voláteis (18,95 mgN/100g); oxidação lipídica (0,58 mg MDA kg-1); e valor energético de 350,55 kcal/100g; além da qualificação de batérias (Staphylococcus xylosus e S. saprophyticus) e fungos (Sterigmatomyces halophilus, Aspergillus cibarius, Cladosporium dominicanum e C. sphaerospermum) presentes. Além disso, a comparação da bottarga produzida pela comunidade da Enseada da Baleia com os valores disponíveis na literatura e em outras bottargas disponíveis no mercado, mostraram similaridade, e comprovam que o produto alvo deste trabalho está dentro da normalidade. A avaliação da qualidade química e microbiológica da bottarga evidenciou oportunidades para aprimoramento do processo produtivo como a aspersão de ácido ascórbico como conservante; a troca no sal utilizado de sal animal para o de consumo humano; e uso de embalagens que garantam melhor vácuo. Os resultados demonstram que a iguaria produzida pela comunidade tradicional caiçara é segura para o consumo humano, além de apresentar ótimos valores nutricionais e se configurar como um importante elemento para o desenvolvimento social e econômico da comunidade, contribuindo para a geração de renda, a preservação da cultura local e a valorização da identidade caiçara. Desta forma, os resultados deste estudo permitem o embasamento necessário para esboço do plano de ações dos próximos trabalhos em busca da otimização da qualidade do produto, constante expansão do mercado consumidor e consolidação da bottarga como importante ativo socioeconômico para a comunidade.

Products produced in a manner known as eco-friendly and that are aligned with at least one of the United Nations Sustainable Development Goals immediately capture the attention of a growing number of consumers. It is in this context that the mullet bottarga is found, produced by hand by the fishing community of Enseada da Baleia, Cananéia – SP. The bottleneck of the production of salted and dried mullet roe is in the form of drying, and the objective of this project is to characterize the production process of chemical and microbiological composition of the bottarga. This work is the initial part of another project, and its function was to establish the parameters of the product before the implementation of improvements in the drought method. The study presented the results of humidity (8.82%); ashes (7.92%); crude protein (43.56%); lipids (19.59%); total solids (91.18%); pH (5.7); volatile nitrogenous bases (18.95 mgN/100g); lipid oxidation (0,58 mg MDA kg-1); and and energy value of 350.55 kcal/100g; in addition to the qualification of bacteria (Staphylococcus xylosus and S. saprophyticus) and fungi (Sterigmatomyces halophilus, Aspergillus cibarius, Cladosporium dominicanum and C. sphaerospermum) present. In addition, the comparison of the Bottarga produced by the community of Enseada da Baleia with the values available in the literature and in other bottarga available in the market, showed similarity, and proved that the target product of this work is within the normal range. The evaluation of the chemical and microbiological quality of bottarga showed opportunities to improve the production process, such as the sprinkling of ascorbic acid as a preservative; the change in the salt used from mineral salt to common salt; and the use of packaging that ensures better vacuum. Even so, the results show that the delicacy produced by the traditional caiçara community is safe for human consumption, in addition to presenting excellent nutritional values and being an important element for the social and economic development of the community, contributing to income generation, the preservation of local culture and the appreciation of the caiçara identity. In this way, the results of this study provide the necessary basis for the outline of the action plan for the next works in search of optimizing the quality of the product and constant expansion of the consumer market and consolidation of bottarga as an important socioeconomic asset for the community.
Nutritional characterization and microbiological investigation of Bottarga produced by the fishing community of Enseada da Baleia – Cananéia, SP
Keywords: Pesca artesanal; Pescado; Ova; Tainha; Valor nutricional; Artisanal fishing; Fish; Roe; Mullet; Nutritional value